Komitmen Perseroan Terbatas Terhadap Pencantuman Klausula Tanggung Jawab Sosial Dan Lingkungan Dalam Akta Pendirian Perseroan Terbatas Di Kota Bengkulu - Elsa Romana Widyarni; Edra Satmaidi; Widiya N. Rosari (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to analyze the commitment of Limited Liability Company (PT) founders in Bengkulu City regarding the inclusion of Social and Environmental Responsibility (TJSL/CSR) clauses in the Deed of Establishment, and to analyze the legal implications for companies that fail to fulfill this obligation. The background of this research is based on the phenomenon of numerous companies in Bengkulu with "Red PROPER" status and problematic Mining Business Licenses (IUP), indicating low compliance with the mandate of Article 74 of Law Number 40 of 2007 concerning Limited Liability Companies. The research method used is empirical juridical with a legal sociology approach. Data were obtained through field research involving interviews with Notaries and Directors/Founders of PTs in Bengkulu City, supported by secondary data from literature studies. Sample determination was carried out using purposive sampling, focusing on companies in the mining and plantation sectors. The results showed that the commitment of PT founders in Bengkulu City regarding the inclusion of TJSL clauses is very low. From all the Deed of Establishment samples examined, no specific inclusion of TJSL clauses was found. This is because the founders view the Deed of Establishment merely as an administrative formality to obtain business licensing (Online Single Submission), and there is a perception that TJSL is a cost burden that reduces profits. The role of Notaries in this matter tends to be passive, merely recording the will of the parties. The legal implications for companies that do not implement TJSL include administrative sanctions ranging from warnings to revocation of business licenses; however, implementation remains ineffective ("paper tiger") due to law enforcers' hesitation regarding economic impacts. Furthermore, there is a potential for civil liability in the form of Tort (Unlawful Act) lawsuits if such negligence causes harm to the community.